Coronary artery event and CYP2C19LoF polymorphism analysis using clopidogrel: A meta-analysis (Asian Journal of Pharmaceutics (AJP), 2025)
Background: Clopidogrel (CLOP) has been used as an antiplatelet medication for many years to treat strokes;however, CLOP resistance may increase the risk of stroke recurrence. The poor metabolism of CLOP, whichleads to resistance, is thought to be caused by the CYP2C19 (C-19) loss of function (LoF) polymorphism. Itwas impossible to draw firm conclusions from earlier research since the data were so inconsistent and diverse.Aim: The current study was conducted to gather conclusive data from an updated meta-analysis about therelationship between C-19LoF(C-19-LoF) polymorphism and coronary artery (CA) events in individuals usingCLOP. Methodology: Electronic databases PubMed, EMBASE, SciHub, and Google Scholar were used to extractdata till November 2024. RevMan 5 software was used for the analysis of extracted data. Results: Out of 7582articles, we used 90 carefully selected to conduct our meta-analysis, which comprised 52,748 patients with CAdisease undergoing CLOP medication. Conclusion: Our results indicate that CA events and composite events aresignificantly more common in individuals with one or more C-19-LoF alleles worldwide than in those withoutthese alleles, particularly in Asian populations. The C-19-LoF alleles put the entire population at risk for compositeevents and recurrent CA events, especially Asians on CLOP, according to our meta-analysis. For people with pooror intermediate metabolic activity, more study is needed on alternate antiplatelet treatments.